Hepatitis B virus infection is associated with deletion of chromosome 8p in multiple myeloma - Becker, Nikolaus; Byl, Anne; Friedrich, Susanne; Jauch, Anna; Schnitzler, Paul; Egerer, Gerlinde; Ho, Anthony Dick; Goldschmidt, Hartmut; Neben, Kai (European journal of haematology, 2013)
Serological analyses within epidemiological cohort and case-control studies indicate to an association between HBV infection and risk of multiple myeloma (MM). To verify the relationship with an independent approach, we investigated the correlation between HBV positivity and chromosomal aberrations within 680 patients of the National Center for Tumor Diseases Heidelberg for which the serological HBV status (HBsAg and anti-HBc) and FISH data for five gains (1q21, 9q34, 11q23, 15q22, 19q13), five losses (6q21, 8p21, 13q14, 17p13, 22q11), and three IgH translocations [t(4,14), t(11,14), t(14,16)] were available. Deletion of 8p21 and 13q14 were shown associated with HBV positivity within hepatocellular carcinoma in other investigations. In the present evaluation, the odds ratio for loss of 8p21 was significantly elevated (OR = 2.74, 95% CL = 1.36-5.50, P = 0.0048) and for loss of 13q14 non-significantly increased (OR = 1.40, 95% CL = 0.74-2.65) in anti-HBc positive patients. The results provide further support for a role of HBV infection in the pathogenesis of MM.
Gesehen am 18.11.2020
First published: 03 October 2012